The shortened Corporate Ethical Virtues scale: Measurement invariance and mean differences across two occupational groups. (30th March 2018) - Huhtala, Mari; Kangas, Maiju; Kaptein, Muel; Feldt, Taru
Abstract: So far, the field of business ethics lacks validated measures for assessing virtues at the organizational level. The aim of this study is to investigate the measurement invariance of a shortened Corporate Ethical Virtues scale. In this manner, we contribute to validating an instrument that is both psychometrically sound and efficient to use. We conducted two survey studies of two independent groups (managers and school psychologists). Confirmatory factor analysis supported the eight‐factor model of the scale, and we found it to be invariant in two different occupational groups. The managers gave higher appraisals of ethical culture than the psychologists did in seven out of the eight dimensions. We found that despite the contextual differences, the shortened scale measures the eight dimensions of organizational ethical virtues, as intended. Thus, the use of this more compact scale can be recommended for future studies, which will hopefully stimulate more research on ethical culture in various work contexts.